Growth Hormone Signaling Pathway Leading to the Induction of DNA Synthesis and Proliferation in Primary Cultured Hepatocytes of Adult Rats - Mitsutoshi Kimura; Kazuki Kurihara; Hajime Moteki; Masahiko Ogihara (Frontiers Media S.A., 2021)
Background: We investigated the signal transduction pathway associated with growth hormone (GH)-stimulated DNA synthesis and proliferation in primary cultured hepatocytes. Methods: Adult rat hepatocytes were isolated from normal livers by two-step in situ collagenase perfusion to facilitate disaggregation of the adult rat liver. Then hepatocytes were cultured in serum-free Williams' medium E supplemented with GH (1-100 ng/ml) in the presence or absence of test reagents. GH-induced hepatocyte DNA synthesis and proliferation were determined, and the phosphorylation activities of Janus kinase (JAK) 2 (JAK2) (p125 kDa), p95-kDa RTK, and ERK1/2 were measured by western blotting. Results: Hepatocytes grown in serum-free defined medium proliferated within 5 h of culture in the presence of GH (100 ng/ml) in a concentration- and time-dependent manner (EC50 75 ng/ml). These proliferative effects of GH were almost completely blocked by an anti-GH receptor monoclonal antibody (85 ng/ml) and an anti-insulin-like growth factor (IGF)-I receptor monoclonal antibody. In addition, the proliferative effects of GH were significantly blocked by a JAK2 inhibitor (TG101209, 10−6 M), as well as specific signal-transducing inhibitors of phospholipase C (PLC; U-73122, 10−6 M), RTK (AG538, 10−6 M), phosphoinositide 3-kinase (PI3K; LY294002, 10−6 M), mitogen-activated protein kinase kinase/extracellular signal-regulated kinase (MEK/ERK; PD98059, 10−6 M), and mammalian target of rapamycin (mTOR; rapamycin, 10 ng/ml). GH significantly induced the phosphorylations of JAK2 (p125 kDa), p95-kDa IGF-I receptor tyrosine kinase (RTK), and ERK2 in this order according to western blotting analysis. Conclusions: The proliferative action of GH is mediated by two main signaling pathways. One includes activation of the GH receptor/JAK2/PLC/Ca2+ pathway, and the other involves activation of the p95-kDa IGF-I RTK/PI3K/ERK2/mTOR pathway in primary cultures of adult rat hepatocytes.